Physical and Chemical Parameters of Estuarine Waters around South Sulawesi - Hasriani Ayu Lestari; Muh. Farid Samawi; Ahmad Faizal; Abigail Mary Moore; Jamaluddin Jompa (Indonesian Journal of Geography, 2021)
Water quality parameters can be indicators of pollution driving riverine, estuarine and coastal resource degradation. This study evaluated water quality in the downstream, estuarine and surrounding coastal waters of 8 major rivers around the western, southern and eastern coasts of South Sulawesi Province, Indonesia. Data on physical and chemical parameters (salinity, temperature, total dissolved solids (TDS), conductivity, turbidity, pH, dissolved oxygen (DO), nitrate and ammonium) were collected during January 2020. These data were interpolated and mapped using the Kriging tool in ArcGIS 9.3 and analysed using the STORET scale and principle component analysis (PCA).  STORET values indicate moderate to heavy pollution, with the most severe pollution in Makassar City. Dominant defining parameters based on the PCA were nitrate, ammonium and DO at the Malili and Makassar sites,  pH, temperature, TDS and salinity at the Palopo, Bulukumba and Pangkep sites, conductivity at the Takalar site and turbidity at the Pinrang site.